ANALISIS PENILAIAN KINERJA MANAJEMEN RANTAI PASOKAN DENGAN BALANCED SCORECARD (STUDI KASUS ASTRA MOTOR MAGELANG 1) - Hermanto, Wachid; Achsa, Andhatu (Fakultas Ekonomi Universitas Gresik, 2021)
In order to achieve a good integration, a supply chain management approach is needed by the company. It aims to achieve an efficient supply chain so that it can control costs. In addition, it is also an effort to improve services to meet customer needs. The purpose of this research is to know the performance of supply chains at Astra Honda Motor to know the flow of Honda products from upstream to downstream and know the performance of supply chain management at Astra Honda Motor. The research was conducted on the company Astra Motor Magelang 1 which is the official Deller of Astra. Analysis of this research data uses Balanced Scorecard analysis. The research was conducted in 2020, using a qualitative descriptive method of describing the phenomenon. And for the use of data for primary and secondary data. Results showed that the excellent supply chain performance that proved from the research results from the perspective of Balance scorecard has a weighted more than average research score. There are only indicators that are still not optimal that is about the level of damage to the product that occurs when distributing. To be able to keep the image of Honda brand, the company must be able to work with maximum performance. Improving the performance of one of the indicators is still a good move.